Time-resolved measurement of neutron energy isotropy in a sheared-flow-stabilized Z pinch - R.A. Ryan; P.E. Tsai; A.R. Johansen; A.E. Youmans; D.P. Higginson; J.M. Mitrani; C.S. Adams; D.A. Sutherland; B. Levitt; U. Shumlak (Nuclear Fusion)
Previous measurements of neutron energy using fast plastic scintillators while operating the Fusion Z Pinch Experiment (FuZE) constrained the energy of any yield-producing deuteron beams to less than 4.65 keV. FuZE has since been operated at increasingly higher input power, resulting in increased plasma current and larger fusion neutron yields. A detailed experimental study of the neutron energy isotropy in these regimes applies more stringent limits to possible contributions from beam-target fusion. The FuZE device operated at −25 kV charge voltage has resulted in average plasma currents of 370 kA and D–D fusion neutron yields of $4×10^7 ± 4×10^6$ neutrons per discharge. Measurements of the neutron energy isotropy under these operating conditions demonstrates the energy of deuteron beams is less than $7.4 ± 5.6^(stat) ± 3.7^(syst)$ keV. Characterization of the detector response has reduced the number of free parameters in the fit of the neutron energy distribution, improving the confidence in the forward-fit method. Gamma backgrounds have been measured and the impact of these contributions on the isotropy results have been studied. Additionally, a time dependent measurement of the isotropy has been resolved for the first time, indicating increases to possible deuteron beam energies at late times. This suggests the possible growth of m = 0 instabilities at the end of the main radiation event but confirms that the majority of the neutron production exhibits isotropy consistent with thermonuclear origin.